Three-dimensional numerical simulation of heat transfer and flow of waxy crude oil in inclined pipe - Lianjie Zhang; Changshun Du; Hongtao Wang; Jian Zhao (Case Studies in Thermal Engineering, 2022)
The purpose of this study is to obtain the heat transfer and flow law of waxy crude oil in the inclined pipeline and to provide theoretical guidance for the safe operation of the pipeline. In this paper, three-dimensional numerical simulation of pipes with inclination angles of 0°, 25 °and 45 °is carried out by using CFD software. The temperature and velocity fields of waxy crude oil and the cooling gelation law of crude oil are basically the same in different cases. Affected by the initial temperature field of shutdown, the average temperature of horizontal pipeline decreases gradually along the flow direction of pipeline. The inclined pipe is mainly affected by the natural convection caused by gravity, and the temperature decreases gradually along the downward direction of the inclination of the pipe. The inclination angle of the pipe increases to 45°, the temperature difference between the highest and lowest points of the pipe increases to 5.012 °C, and the liquid volume fraction increases by 1.6%. Among them, the low-lying pipe section is more likely to cause pipeline blockage.